2008
DOI: 10.2139/ssrn.965765
|View full text |Cite
|
Sign up to set email alerts
|

Momentum, Size and Value Factors versus Systematic Co-Moments in Stock Returns

Abstract: Further information on publisher's website:http://www.dur.ac.uk/business/faculty/working-papers/ Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…and Chung et al (2006) and Hung (2008) demonstrate that comoments above the fourth order are priced. Accordingly, we attempt to identify the realized comoment above the fourth-order under the arithmetic sense.…”
Section: Introductionmentioning
confidence: 97%
“…and Chung et al (2006) and Hung (2008) demonstrate that comoments above the fourth order are priced. Accordingly, we attempt to identify the realized comoment above the fourth-order under the arithmetic sense.…”
Section: Introductionmentioning
confidence: 97%
“…Also, recent research has suggested that the size and book-to-market factors of Fama and French (1996), which explain the size effect first documented by Banz ( 1981), may be proxies for higher-order systematic co-moments of returns (Chung et al, 2006). In addition, Hung (2007) shows that both momentum and size effects are partly attributable to coskewness and cokurtosis risks. Fuertes, Miffre and Tan (2005) also point out that momentum returns are related to non-normality risk.…”
Section: Introductionmentioning
confidence: 97%
“…Chung, Johnson and Schill (2006) suggest that the size and book‐to‐market factors of Fama and French (1996), which explain the size effect documented by Banz (1981), may be proxies for higher‐order systematic co‐moments of returns. In addition, Hung (2008) shows that both momentum and size effects are attributable to higher‐order systematic co‐moment risk.…”
Section: Introductionmentioning
confidence: 98%